The Effect of Product Design and Country of Origin on Purchase Decisions: The Moderating Role of Price Discounts in Mitsubishi Electric Air Conditioners - Risna Evelina Sirait; Rezky Alamsyah; Romeo Gary Ruben Siregar; Bambang Suwarno (International Journal of Science and Environment (IJSE), 2026)
This study analyzes the effect of product design and country of origin on purchase decisions, with price discount as a moderating variable, in the context of Mitsubishi Electric air conditioners in Medan, Indonesia. A quantitative explanatory approach was applied using purposive sampling. Data were collected from 400 consumers who had purchased Mitsubishi Electric air conditioners and were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings indicate that product design and country of origin do not significantly influence purchase decisions. In contrast, price discount has a strong and significant positive effect on purchase decisions. The moderating role of price discount on the relationship between product design and purchase decision is not supported. These results suggest that economic considerations, particularly promotional pricing strategies, are more influential than intrinsic product attributes or country-of-origin perceptions in shaping consumer decisions about durable home electronics in competitive markets.